2023
DOI: 10.1111/1365-2664.14429
|View full text |Cite
|
Sign up to set email alerts
|

Effective management for deadwood‐dependent lichen diversity requires landscape‐scale habitat protection

Abstract: Habitat loss is considered a major threat for biodiversity. However, the scales on which its effects occur are still insufficiently understood, namely, is the amount of available habitat important for species richness on both local and landscape scales? We studied the effects of local and landscape‐scale habitat amount on local‐scale species density of deadwood‐dependent lichens in Swedish boreal forests. Creation and retention of deadwood are common practices to benefit forest biodiversity, and recognizing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
3
2
Order By: Relevance
“…This is in contrast with the habitat amount hypothesis (Fahrig 2013), which predicts that the focal patch area should not affect species density within a sample area, when the landscape habitat amount has been accounted for. Furthermore, it is in contrast with a previous study that did not observe any effects of local dead wood amount on lichen species density in old pine forests (Hämäläinen et al 2023). Our result implies that larger patches of old forest can maintain higher local species density, at least in some regions.…”
Section: Effects Of Habitat Amount Fragmentation and Stand-scale Vari...contrasting
confidence: 99%
See 3 more Smart Citations
“…This is in contrast with the habitat amount hypothesis (Fahrig 2013), which predicts that the focal patch area should not affect species density within a sample area, when the landscape habitat amount has been accounted for. Furthermore, it is in contrast with a previous study that did not observe any effects of local dead wood amount on lichen species density in old pine forests (Hämäläinen et al 2023). Our result implies that larger patches of old forest can maintain higher local species density, at least in some regions.…”
Section: Effects Of Habitat Amount Fragmentation and Stand-scale Vari...contrasting
confidence: 99%
“…old forest, in the landscape had in most cases a positive effect on the species density of deadwood-dwelling lichens. However, these effects were rarely significant, and typically quite weak in comparison to previous studies that have found lichen diversity to increase with landscape habitat amount in boreal (Kärvemo et al 2021;Hämäläinen et al 2023) and temperate forests (Paltto et al 2006). Moreover, in some cases, the present amount of habitat in the southern study region had a negative (though weak) effect on lichen species density.…”
Section: Effects Of Habitat Amount Fragmentation and Stand-scale Vari...contrasting
confidence: 71%
See 2 more Smart Citations
“…Furthermore, the structural-functional role of deadwood in forests has been widely recognized by the scientific community and decision makers in the last two decades [15]. Numerous studies have shown the importance of deadwood as microhabitats for saproxylic insects [16], fungi [17], bacteria and actinobacteria [18], bryophytes [19], lichens [20], amphibians [21], small mammals [22], and birds [23].…”
Section: Introductionmentioning
confidence: 99%